2020
DOI: 10.1007/s00330-020-06776-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics for lung adenocarcinoma manifesting as pure ground-glass nodules: invasive prediction

Abstract: Objectives To investigate the value of radiomics based on CT imaging in predicting invasive adenocarcinoma manifesting as pure ground-glass nodules (pGGNs). Methods This study enrolled 395 pGGNs with histopathology-confirmed benign nodules or adenocarcinoma. A total of 396 radiomic features were extracted from each labeled nodule. A Rad-score was constructed with the least absolute shrinkage and selection operator (LASSO) in the training set. Multivariate logistic regression analysis was conducted to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 29 publications
1
92
1
Order By: Relevance
“…Eguchi et al examined 124 cases with pGGNs, and 64 pGGNs (51.6%) showed growth during their 2-year follow-up (7). Several previous research revealed that nearly 50% of pGGNs were invasive lesions (3,(8)(9)(10). In clinical practice, pGGNs are usually prescribed to be followed up but data above demonstrated that more detailed diagnosis and more individualized management should be made for pGGNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eguchi et al examined 124 cases with pGGNs, and 64 pGGNs (51.6%) showed growth during their 2-year follow-up (7). Several previous research revealed that nearly 50% of pGGNs were invasive lesions (3,(8)(9)(10). In clinical practice, pGGNs are usually prescribed to be followed up but data above demonstrated that more detailed diagnosis and more individualized management should be made for pGGNs.…”
Section: Discussionmentioning
confidence: 99%
“…According to the new classification, lung adenocarcinoma can be divided into preinvasive lesion, minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IVA), and preinvasive lesion includes atypical adenomatous hyperplasia (AAH) and adenocarcinoma in situ (AIS) ( 1 ). The improvement of medical technology and the generalization of lung cancer screening project have led more attention to pure ground-glass nodules (pGGNs) detected on computed tomography (CT) images ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…I. P. Hwang et al [18] used texture analysis to distinguish IAs from pre-invasive lesions and MIAs manifesting as persistent pGGNs with a diameter of >5 mm, and the model showed good classification performance with an area under the ROC curve (AUC) of 0.962. Furthermore, some studies [19,20] have demonstrated that a mixed clinical radiomics model provides better discrimination between invasive lesions (MIAs/IAs) and pre-invasive lesions than the standalone clinical model. However, none of these studies reported the specificities of radiomics for identifying MIAs and IAs in pGGNs or the use of a cut-off size of 10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for the prediction between AIS/MIA and IAC representing as pGGNs, Xu et al [ 34 ] showed the predictive radiomics models built in study (AUC 0.833;95% CI, 0.733–0.934) which provided a good predictive power. Besides, Sun et al [ 35 ] developed a radiomics-based Rad-score utilized as a biomarker for the invasiveness-predicted evaluation in patients with pGGNs (AUC 0.72; 95% CI, 0.63–0.81). Their study confirmed the advantage of radiomics in the diagnosis of Benign/AAH/AIS from MIA/IAC.…”
Section: Discussionmentioning
confidence: 99%